2008
DOI: 10.1093/jn/138.5.908
|View full text |Cite
|
Sign up to set email alerts
|

Almonds Reduce Biomarkers of Lipid Peroxidation in Older Hyperlipidemic Subjects ,

Abstract: Nut consumption has been associated with reduced coronary heart disease (CHD) risk. In addition to cholesterol-lowering properties, almonds have been shown to lower oxidized LDL concentrations. However, little is known regarding their effects on other markers of oxidative stress. The dose-response effects of whole almonds, taken as snacks, were compared with low-saturated fat (<5% energy) whole-wheat muffins (control) in the therapeutic diets of hyperlipidemic subjects. In a randomized crossover study, 27 hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 52 publications
2
92
1
4
Order By: Relevance
“…Recent well controlled intervention studies with walnuts [71,72,73,74], almonds [75], hazelnuts [76], pistachios [77], macadamias [78], and peanuts [79] showed LDL-cholesterol reductions ranging from 4% to 11% versus comparator diets, confirming the cholesterol-lowering efficacy of various nut types. A Mediterranean diet supplemented with 30 g of mixed nuts (walnuts, almonds and hazelnuts) per day also showed beneficial effects on the lipid profile compared with advice on a low-fat diet in diabetic and non diabetic participants in the PREDIMED study, a randomized trial of dietary intervention for the primary prevention of cardiovascular disease [80].…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 93%
“…Recent well controlled intervention studies with walnuts [71,72,73,74], almonds [75], hazelnuts [76], pistachios [77], macadamias [78], and peanuts [79] showed LDL-cholesterol reductions ranging from 4% to 11% versus comparator diets, confirming the cholesterol-lowering efficacy of various nut types. A Mediterranean diet supplemented with 30 g of mixed nuts (walnuts, almonds and hazelnuts) per day also showed beneficial effects on the lipid profile compared with advice on a low-fat diet in diabetic and non diabetic participants in the PREDIMED study, a randomized trial of dietary intervention for the primary prevention of cardiovascular disease [80].…”
Section: Nut Feeding Trials With Outcomes On Cardiovascular Risk Fmentioning
confidence: 93%
“…Population studies indicate that individuals who regularly consume nuts have reduced risk for cardiovascular diseases and diabetes [1] . The beneficial role of almonds has been established with respect to serum lipid profile [2] however, its beneficial effects on glycemia are still to be established.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta‐analysis of 18 randomized controlled trials has shown that intake of almonds improved the lipid profile by decreasing total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), and triglycerides 6. Furthermore, almonds improve other cardiovascular risk factors, including insulin resistance,7 endothelial dysfunction,8 inflammation,9 and oxidative stress 10…”
mentioning
confidence: 99%